Evaluasi Usability Web UniPin dengan Menggunakan Metode Usability Testing - Dinda Aditya Febrianti; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
E-commerce is an online shopping activity service using the internet network as well as how to do transactions through digital money transfers provided by PT. 24 Hours Online (UniPin). On the UniPin website there are tons of games that have collaborated with unipin.co.id such as the Mobile Legends game, PUBG Mobile, besides the UniPin web also provides Google Play vouchers, Steam Wallet and other vouchers. UniPin is a business that has been started since 2009 and already has millions of users. From the data of user complaints, there are several problems regarding aspects of usability, such as the user not understanding the UniPin web usage flow. According Istiana (2015) Evaluation of usability of a website that has been built needs to be done one of them to find out how the usability of the website for users. To find out the level of usability on the e-commerce website used by PT. 24 Hours Online, it is necessary to evaluate usability on the UniPin website by using the usability testing method to observe user behavior. To obtain data, the data collection techniques used are by observing user behavior when carrying out the given task and conducting questionnaires using the Nielsen Attributes of Usability (NAU) questionnaire, and interviews with UniPin web users. The usability evaluation process consists of several stages, including extracting information by requesting customer complaint data on the UniPin web customer service, assigning tasks to respondents, filling out questionnaires, interviewing respondents to dig deeper information, the data obtained is then processed using the Likert scale method and in the analysis, then the UniPin web display design is made according to the analysis obtained. Based on the analysis, the results for the learnability aspect were 77%, the efficiency aspect was 75%, the memorability aspect was 79%, the error aspect was 71%, and the satisfaction aspect was as much as 70%. This shows that the results of the UniPin web usability level research are still in the agreed / good / like interval criteria, and produced 3 UniPin web display mockups that can be used to help improve the UniPin web.